A description of the characteristics at presentation of children diagnosed with Diabetes Mellitus from 2005-2009 at Red Cross War Memorial Children's Hospital - Botes, Alida Maria (Department of Paediatrics and Child Health, 2017)
Objective: To document the demographics, the pattern of clinical and laboratory characteristics at the time of diagnoses for all the newly diagnosed diabetics younger than 14 years reviewed at the Diabetic clinic at the Red Cross War Memorial Children's Hospital (RCWMH) during 2005-2009. Method: A retrospective folder review was done of all the newly diagnosed diabetics younger than 14 years old at the age of diagnosis. 225 patients were included for analysis. Patients were grouped according to age into a young group (1 month to < 5 years old), a middle group (5years - < 9 years) and an older group (9years - <14 years). Neonates were excluded as well as children who became diabetic secondary to another condition. Results: 58% of the patients were female and most of the patients were diagnosed with type 1 diabetes (96%). The median age at diagnosis was 8.5 years with a mean HbA1c of 11, 3%. 68% of the patients were in the normal weight category while 8, 4% of the patients were obese. 148 (65%) of the 225 patients presented in diabetic ketoacidosis (DKA). Only one of the patients classified with type 2 diabetes presented in DKA. 51 (22,67%) of the patients were less than 4 years old at the time of diagnosis. 53% of the Caucasian children were less than 4 years old at diagnosis while most of the children in the black and coloured group were diagnosed after 10 years of age. A seasonal variation was seen especially in the young age group with 66% presenting in autumn or winter months. Conclusions: Almost a quarter of diabetic children presented before the age of 4 years. A large proportion of patients presented in diabetic ketoacidosis which can be life threatening. Due to lack of information at diagnosis, this could be under reported significantly and calls for increase awareness amongst physicians and parents to recognise symptoms earlier. Prospective studies on childhood diabetes in South Africa are needed as well as a registry for childhood diabetes.